2023
DOI: 10.3390/ma16175924
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Deterioration Mechanism of Magnesium Oxychloride Cement under an Alkaline Environment

Lingyun An,
Chenggong Chang,
Fengyun Yan
et al.

Abstract: The deterioration process and deterioration mechanism of magnesium oxychloride cement (MOC) in an alkaline environment were studied using a scanning electron microscope (SEM), an X-ray diffractometer (XRD), a Fourier transform infrared spectrometer (FT-IR) and a micro-electro-hydraulic servo pressure testing machine to investigate the effects of soaking time in 10 wt.% NaOH solution on the macro- and micro-morphology, phase composition and compressive strength of MOC samples. The results show that the deterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It significantly degrades in a moist environment as a result of the leaching of MgCl 2 , causing a loss in strength. Existing research has revealed that the compressive strength drastically decreases when MOC is soaked in water, owing to the transition of phases 3 and 5 [16,17]. In consequence, the damaged matrix also considerably accelerates the process of water infiltration, increasing deterioration and creating a vicious circle of continuing damage [18].…”
Section: Introductionmentioning
confidence: 99%
“…It significantly degrades in a moist environment as a result of the leaching of MgCl 2 , causing a loss in strength. Existing research has revealed that the compressive strength drastically decreases when MOC is soaked in water, owing to the transition of phases 3 and 5 [16,17]. In consequence, the damaged matrix also considerably accelerates the process of water infiltration, increasing deterioration and creating a vicious circle of continuing damage [18].…”
Section: Introductionmentioning
confidence: 99%